Perancangan dan Implementasi Sistem Pendukung Keputusan Untuk Penjurusan Siswa Menggunakan Metode Jaringan Saraf Tiruan Studi Kasus di MAN 2 Padang Panjang - Bobby Rachman; yeka Hendriyani; Khairi Budayawan (Universitas Negeri Padang, 2016)
A Constraint in education order to produce qualified graduates is a traditional mindset of many schools in students’ majoring which only emphasizes on students’ grades. The fact is similar to ideas that expressed by Seto Mulyadi (2003), a practitioner of the child's education. He said that it was a big mistake if student achievement only measured on grades at the end of the semester.Senior High school is upper level of formal education in Indonesia, after graduating from junior high school. Students study at senior high school within 3 years as they study at Islamic senior high school (MAN) 2 Padang Panjang, ranging from grade 10 to grade 12. In the second year or at the grade 11, students may choose one of the majors that exist in schools, namely, science, social, and Religious. In designing the decision support system for students’ majoring at MAN 2 Padang Panjang, an artificial neural network based on Multiple Intelligence is needed. Furthermore, Java programming and MySQL are also required. The results of the data analysis showed that the design of a decision support system for students’ majoring at MAN 2 Padang Panjang by using artificial neural network was successfully implemented, and the system can help the teachers to simplify the implementation of students’ majoring. Keywords: Students’ majoring, Multiple Intelligence, Artificial Neural Networks, Java and MySQL